Design of Semujur Bridge with Diagonal Steel Box Arch Bridge - Alghiffary, Rizqi; Junianda Velantika, Griselda; Eka Putri, Karina Melawati; Dewi Widowati, Elok; Fauzan Akbari, Muhamad (International Journal of Engineering, Science and Information Technology, 2025)
Transportation is an integral part of social life. One of the structures that can support transportation is the bridge. The construction of the Semujur Bridge will be planned to meet and support transportation needs. This bridge is expected to be a new connecting bridge to cut travel time in Pangkal Pinang City. Semujur Bridge, with a width of 20 meters and a total length of 100 meters, is planned to use a steel arch bridge because the arch bridge can reduce the bending moment on the bridge. The bridge uses a box girder cross section because the arch bridge with a steel box cross-section is considered more economical and has higher flexural strength and torsional stiffness. Semujur Bridge will also have a diagonal arch. With the new construction design, it is expected to be a structurally strong bridge, both against earthquake loads and bridge dynamic loads. As a result, in this study, it was found that the longitudinal girder WF 600x300x14x23, transverse girder GIRDER 1500x400x30x30, tie beam BOX GIRDER2500x2000x40x40, and Macalloy 520 (M100) hanging cable with a diameter of 97 mm.